A STUDY OF SATISFACTION LEVEL AND OPINION ABOUT THE TRAINING AND DEVELOPMENT PROGRAM IN THE ORGANISATION - Rozario, Kevin (The journal of contemporary issues in business and government, 2021)
The aim of this paper is to introduce a study developed in the training and staff development program and its benefits in the organisation. This study will explore the design and components of anemployee training and development program and over time the research will outline the best results for employees and the organizations. Organizations find it difficult to stay economical in the latest global economy. The significance of the human resource development program is rising in the organizations that seek to make a profit between competitors. Employees are respected organizational performance and the victory or failure of the organization extends to the performance of employees. However, organizations are investing heavily in staff training programs and development programs. In addition, the training program supports companies to put emphasis on the knowledge, expertise and skills of employees. There is a great deal of discussion between experts and researchers about the impact of that development programs on both staff and the organization. The research defined here is an in-depth examination of the literature on the critical process of human resource development and its welfares to organizations and employees.